2021
DOI: 10.3390/ijerph18179007
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals (As, Cd, Cr, Cu, Hg, Ni, Pb, Zn) and Stable Isotope Ratios (δ13C and δ15N) in Fish from Wulungu Lake, Xinjiang, China

Abstract: Wulungu Lake is a vital fishery area in Xinjiang. However, the concentration, enrichment rules, and sources of As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn in the aquatic organisms, have rarely been investigated. The results suggest that the concentrations of As, Ni, Pb, and Zn were higher than those recommended by the national standards for edible fish in some species. Hg, Ni, Cu, Pb, Cr, and Zn in the fish were dependent on the concentration of trace metals in the water environment (p < 0.05). The body weights of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The APLI approach is used to assess the harmful effects of different metals on exposed [ 32 ] freshwater, coastal and marine fishes, the following formula is used in Eq. (2) .…”
Section: Methodsmentioning
confidence: 99%
“…The APLI approach is used to assess the harmful effects of different metals on exposed [ 32 ] freshwater, coastal and marine fishes, the following formula is used in Eq. (2) .…”
Section: Methodsmentioning
confidence: 99%
“…The average pollution load index (APLI) approach is used to evaluate the possibly harmful effects of studied metals in exposed vegetable and fish species ( Liu et al., 2021 ), the following formula is used in Eq. (1) .…”
Section: Methodsmentioning
confidence: 99%
“…(1) . where APLI indicate metals and metalloids contamination in fish and vegetable samples; n represent the number of metals and metalloids; C i is the mean value of metals and metalloids measured in fish and vegetable samples; S i is the maximum admissible concentration (MAC) of metals and metalloids ( Table 2 ); the greater the PI value suggested that the fish and vegetable is not consumable ( Liu et al., 2021 ). Based on the metals and metalloids concentration in fish and vegetable species, the PI < 0.1, 0.1–0.2, 0.2–0.5, 0.5–0.7, 0.7–1.0, >1.0, unpolluted; micro pollution; lightly polluted moderately, polluted; moderately polluted; heavily pollution; seriously polluted, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, these trace elements play an essential role in human visual physiological function [ 16 ]. The absence or excess of trace elements may lead to various diseases [ 17 , 18 ]. For instance, insufficient iron levels can result in anemia, inadequate iodine intake can lead to thyroid disorders, and a deficiency in zinc can cause the dysfunction of retinal cells, contributing to the development of diverse eye diseases [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%